PENGARUH PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Anggririawan, Budi (KRISNA: Kumpulan Riset Akuntansi, 2020)
The purpose of this study was to determine the effect of the principles of good corporate governance on financial performance in the LPD in Abiansemal District, Badung Regency. The sample in this study amounted to 34 LPD with 68 respondents. The data analysis technique used is multiple linear regression, and previously tested research instruments and the classic assumption test for the accuracy of the results of the regression analysis. The results of hypothesis testing indicate that the principles of good